Opodatkowanie dochodów z kapitałów pieniężnych - Kosidłowska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The aim of the paper was to present issues related to the natural person capitalgains tax, in particular legal conditions underpinning the tax and issues relatedto the impact of the tax on state budget revenues. Natural person capital gainstax value in Poland was also analyzed. The study covered the period from 2006until 2013.